A Method of Measuring AC HV Using HV Standard Capacitor - Chen Jie; Hou Xian-Hua; Zhou Li; Zheng Huan; Li Chen-Ying; Li Zhong-Hua (MATEC Web of Conferences, 2016)
According to the demand of new measuring AC high-voltage technology based on the development of power network, this paper proposes an AC high -voltage measuring system using high voltage standard capacitor based on the analysis of the existing AC high-voltage measuring technology, the working principle of the AC high-voltage measuring system is analyzed in detail, and the experimental research on the steady state characteristic and frequency characteristic of the AC high-voltage measuring system is made, at the same time, the possible errors are analyzed in detail. The AC high-voltage measuring system meets the technical requirements of high-voltage signal acquisition in the power system, at the same time, meets the requirements of AC high voltage measurement when the frequency is not more than 2500Hz, and has certain practical value..